A Study Of Some Characteristics Of Religious Composition Of Religious Regions In India - SINGH, Dr. MAUKAM (The journal of contemporary issues in business and government, 2020)
"Religion" is defined as a set of basic ideas and practices that unite people together and are linked together in a universe, in an orderly world. It has roots in the Latin word "ligare" to bind all aspects of the life of its adherents and permeates them. As an immense country, India has a number of people with different faiths that represent a rainbow of religion. In an Indian’s daily and socio-economic and political life, religion plays a vital role. This paper discusses seven Indian religious groups’ spatial concentration. For each religious group, areas of majority and minority (<50% share) are established by taking the district as a space unit to detail the concentration at a district level. The location quotient is also measured for each religious group by spatial concentration. At district level, minority and binary majority are explained. Secondly, this paper tries to develop religious regions of India for seven religious groups, using a cluster analysis technique, to examine religious cohesion and segregation of the Indians. The Hindus are the largest group followed by Muslims, Christians, Sikhs and Buddhists, while Jains are insufficient to demonstrate their presence in India’s religious regions.